Identification of Planktones in Digestion of Seluang (Rasbora sp.) from The Musi River Downstream - Elva Dwi Harmilia; Khusnul Khotimah; Ando Kasmaran (Universitas Muhammadiyah Palembang, 2022)
Utilization of seluang fish (Rasbora sp.) for food and collection by the community as decorative fish to serve as a source of income. The objective of research on the identification of plankton in the digestion of seluang fish from the Musi river downstream is to determine the type of plankton ingested by seluang fish, phytoplankton or zooplankton, which are seluang fish's natural food source. Prior to domestication, plankton variations can be exploited for cultivation efforts as a source of knowledge. The study was conducted in May, June and July 2019 at three stations. Samples of fish caught were observed in the Biology laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang. The fish is dissected using a scalpel, and its digestion is put in a small jar containing a 10% formalin solution. The fish digestion was formalized, transferred into a measuring cup with the addition of 10 ml of an aqueduct, stirred until crushed and observed under a microscope using a petri dish. The study results showed that the seluang fish species (Rasbora sp.) caught were Rasbora argyrotaenia and Rasbora borapetensis. In digestion, there are phytoplankton consisting of 4 classes, namely Cyanophycea, Chlorophyceae, Bacillariophyceae, and Eugleanophycea, while in zooplankton, only one class is found, namely Entomostraca. The composition of phytoplankton is greater than that of zooplankton of the class Cyanophyceae predominating by 34.7%. Thek-index of plankton diversity in digestion is moderate, the biota community is stable, and the dominance index indicates species dominate at each station. Water quality is relatively normal only at station 2, with the value of dissolved oxygen and low-value pH. The phytoplankton composition is greater than that of zooplankton.